Towards a Learning Progression of Alternative Energy at School: A Literature Review - Liandha Arieska Putri; Diana Rochintaniawati; Ida Kaniawati; Anna Permansari (Jurnal Penelitian Pendidikan IPA, 2024)
The enormous energy crisis due to the high demand for energy consumption leads to the need to incorporate Sustainable Development Goals (SDGs) into the learning strategy to ensure energy-literate citizens. This study addressed the analysis of the current trends of alternative energy education in the school setting in terms of educational level scope, content area, and educational strategy. The data was gained from the Scopus database and the PRISMA method which includes the identification, screening, and inclusion phase was used. 15 articles were brought to the inclusion phase to be read and analyzed. The result highlighted that the educational level covered in alternative energy education mainly focused on secondary and university levels. It is found that at elementary and high school levels, there are insufficient amounts of alternative energy education happened. Most of the papers covered general alternative energy as the topic and the rest of the articles mainly focus on one type of alternative energy topic. Project-based learning was the most common educational strategy in teaching alternative energy and STEM learning comes as the second common. Pedagogical, professional development, problem-based learning, and virtual lab were also utilized to teach alternative energy